"Mus vienija alus ir pergalės"? arba Sportas ir lietuviškoji tapatybė - Butautas, Ingvaras; Čepaitienė, Rasa (Lietuvos istorijos studijos, 2006)
Having reached its strategic objectives (membership in the EU and NATO), Lithuania encountered the problem of a trawl for new societal development visions. That is why the Lithuanian mentality, facing such strong challenges as EU integration and globalization, is in quest of national identity components "inventory" and reevaluation in the context of new circumstances. In this regard, sport, universally accepted as a substantial component of national identity, becomes actual for knowledge. Unfortunately, in Lithuania by now, academic writing on this subject astonishes at its fragmentary nature and confines it mainly to the factography, while sport-minded individuals are professionally over-engaged. Therefore, preliminary research has shown that sport, as a socio-cultural phenomenon in the field of interdisciplinary studies, is non-existent in Lithuania. Considering what has been said, we may state decisively that the present article will be one of the first attempts to define and evaluate the role of sport in society and the sphere of politics in a broader way. It will also be the first attempt to search for the roots of broadly entrenched stereotypes and assessments about the involved subject.One of the most vivid stereotypes that embody Lithuanian sport specifics is the affirmation that basketball is the Lithuanian national religion. Paradoxically, Lithuanians fancy themselves due to basketball victories, but perhaps they are better known for football defeats. In opposition to the rest of Europe, basketball truly is the most popular sport in Lithuania, yet till now, nobody has tried to analyze the historical and socio-cultural reasons for such a phenomenon in a more thorough way. In 2003, after a 64-year long break, the Lithuanian national basketball team won the European championship golden medals. That stimulated strong, but momentary manifestations of "emotional community." The last-mentioned victory was turned to account by politics for political needs (for instance, political image mintage) not related to the victory itself. In turn, everybody who was engaged with "extrinsic" state affairs at the moment of triumph was criticized. The symbolic "appropriation" of past and present sport achievements assumes various forms in politics. A characteristic example is the first in Europe impeached President Rolandas Paksas, who during his election campaign successfully played on his acrobatic flying qualifications, thus refreshing a strong association in historical consciousness connected with the interwar period Lithuanian heroes S. Darius and S. Girėnas, who overflew the Atlantic.During the Soviet times, sport had to serve state image and communist ideology needs. Nevertheless, Lithuanians had been trying to round representative commands on republican and local levels (incorporating local foreign-born). In the Soviet Union, something similar was maybe succeeded only by Georgians and Armenians. So we may raise a hypothesis whereby the last-mentioned ability reflects Lithuanian communist leaders and/or sport functionaries' acceptance of such kind of "nationalism." Although the present affirmation is difficult to prove without deeper investigations, it played a crucial role, in contrast to other Soviet republics, in sustaining and reinforcing Lithuanian national identity under the circumstances of Sovietization. The same sportsmen's political-ideological stance was of no particular importance because the main thing was the openness of the same victory to the nation's treatments about resistance to the occupant (victories over CSKA like victories over the Soviet army, and victories over Dinamo like victories over the KGB). Hereby in Lithuania, sport obtained the same strain of cultural resistance. After regaining independence, Lithuanian sport was forced to switch from state-regulated infrastructure to the private sector. This process was painful. More than one and a half years of lasting boycott of international sports federations almost ruined the Lithuanian sport system. Sudden changes harmed the sphere of sport much stronger than other reformatted spheres. Recovering from the boycott-induced crisis, not every branch of sport managed to adequately readjust to the new conditions. In comparison with the Soviet times, management, advertisement, and mass media created images of separate branches of sports and sportsmen, playing a huge role in this sphere today. An illustration of this is the growing gap between the fast crisis-overcoming basketball and other fields of sport (especially football, which due to weak management, lost its once-possessed high rates). Today, interest in sports is highly reduced. That can be attributed to the tenacious Lithuanian habit of linking sports with contraposition to foreigners. Till now, the tendency still persists to take more interest in Lithuanian participation in international competitions than in national championships. The latter are becoming an object of interest for a very small part of society (the only exception might be the Lithuanian basketball league super final, which usually reflects the animosity between the two biggest towns: Vilnius and Kaunas). In turn, the marginal fan groups, which kept a clear nationalistic orientation from Soviet times, have an ideological potential to migrate towards Euro-skepticism, anti-globalism, and xenophobia. Regardless of the huge former importance of sport in sustaining national identity, nowadays, only in case of a signal victory, sport is able to rally strong "emotional communities." As a matter of fact, modern-day Lithuanian general public's interest in sports is rather occasional, maybe even an accidental phenomenon that possesses no endurance in daily life. The "sport-loving nation" stereotype was shaped by mass media because even sports contest visiting rates, generally mouthy and inflated in official protocols, prove the slight popularity of sport in Lithuania in comparison with other East-Central European countries.